CURRENT TRENDS IN THE DEVELOPMENT OF THE INNOVATIVE ENVIRONMENT OF THE DIGITAL ECONOMY IN UKRAINE - Татарчук, Роман Тарасович; Сімків, Ліля Євгенівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
This article examines the key factors of the development of the digital economy, the evolution of the innovative environment of the digital economy, the main technological and social trends in the development of the innovative environment of the digital economy, the problems of the development of the innovative environment of the digital economy and ways to solve them. It was found that the level of development and the level of use of the digital economy in modern conditions play a decisive role in ensuring the country’s competitiveness. The article examines the significance of the processes of formation and development of the innovative environment of the digital economy, which is generally recognized and is a key driver for qualitative changes in the welfare of the state. In innovative renewal, digital resources are a means of achieving goals and determine the entire content of the innovative environment. The article examines a direct ecosystem approach and the basic principles of forming an innovative environment. Key trends in the development of the innovation environment are considered, namely technological innovations such as the Internet of Things, cloud computing and big data, robotics, artificial intelligence and machine learning. These trends reflect the active development of the digital economy and contribute to the creation of an innovative environment that can quickly adapt to the changes and challenges of the modern world. The need for the fastest possible transformation of the entire communication system among the participants of innovative processes in the digital environment has been revealed. The level of the innovation environment in Ukraine and the principles of the development of the digital economy, in particular the development of the Ukrainian innovation ecosystem, the multifaceted government policy of innovation support and innovation stimulation, and the development of technologies that solve the pressing problems of the present and the future have been studied. It was determined that one of the strategic goals of Ukraine is the development of the digital economy, which is characterized by the growth of the economic efficiency of the economic activities of subjects due to the use of the achievements of digitalization of society. Despite the long pause due to the pandemic and the war, new technological trends have formed in Ukraine, which will determine the further development of the innovative environment of the digital economy.